Protective Role of Somatostatin in Sepsis-Induced Intestinal Barrier Dysfunction through Inhibiting the Activation of NF-κB Pathway - Xin Xu; Quanli Zhu; Guoliang Li; Junjian Ma; Zhijian Pan; Wei Wu (Gastroenterology Research and Practice)
Somatostatin (SST) has a protective role in intestinal injury, inflammatory response, and intestinal mucosal barrier in rats with acute pancreatitis. However, its function in sepsis-induced intestinal barrier dysfunction remains largely unknown. A mouse sepsis model was constructed, and SST was injected into the tail vein. Then, hematoxylin and eosin staining (HE) was used to detect the intestinal barrier dysfunction. Enzyme-linked immunosorbent assay was used to detect the level of tumor necrosis factor α- (TNF-) α, interleukin- (IL-) 6, and interleukin- (IL-) 10 in the ileum. Expressions of tight junction proteins, zonula occludens- (ZO-) 1 and Claudin-1, and NF-κB p65 in the ileum were detected using western blot and immunohistochemistry as needed. Furthermore, JSH-23 as an inhibitor of the NF-κB pathway was injected into sepsis mice with SST or not. Mice with sepsis showed an obvious intestinal barrier dysfunction with decreasing specific somatostatin receptor subtype (SSTRs), and increasing TNF-α, IL-6, and IL-10 in the ileum. SST could relieve the injury, the decrease of SSTRs, and the increase of TNF-α and IL-6 induced by sepsis and also further enhanced the expression of IL-10. Further analysis showed that ZO-1 and Claudin-1 were reduced in the ileum by sepsis but enhanced by SST. NF-κB p65 was promoted in the ileum by sepsis but inhibited by SST. Further experiments confirmed that NF-κB inhibitor JSH-23 could repair the intestinal barrier dysfunction and enhance the protective effect of SST on the intestinal barrier. SST, with a protective effect on intestinal barrier dysfunction through suppression of NF-κB, could be a potential therapeutic drug for sepsis-induced intestinal barrier dysfunction.